Interpenetrating covalent adaptable networks with enhanced mechanical properties and facile reprocessability and recyclability. Issue 28 (28th June 2021) - Lei, Yufeng; Zhang, Anqiang; Lin, Yaling
Abstract : An interpenetrating covalent adaptable network is facilely prepared, reprocessed and recycled by exploiting covalent reversible chemistry of imines and boronic-esters. Abstract : Polymer blending has always been a critical strategy for preparing high-performance materials. By creating an interpenetrating polymer network (IPN), the incompatibility of different polymers could be overcome and a favorable bicontinuous phase structure could be achieved. Recently, the concept of covalent adaptable networks (CANs) based on reversible covalent bonds has brought many opportunities for developing and engineering sustainable high-performance polymer blends. Herein, we utilized the reversible hydrolysis/condensation of imines and boronic-esters to construct an interpenetrating covalent adaptable network (IPCAN) with a highly uniform phase structure from two immiscible single CANs, and to establish a closed loop between recycling single networks and regenerating IPCANs as well. The resultant IPCANs show not only a remarkable improvement in mechanical performance, but also a high restoration efficiency during multiple reprocessing. The outcomes of this work may provide new ideas for developing more sustainable high-performance polymer blends and IPNs with covalent reversible bonds.